Among slow dwarfs and fast giants : a systematic design space exploration of KECCAK - Jungk, Bernhard. (2013)
The SHA-3 competition ended in late 2012 by announcing KECCAK as the winning algorithm. During the contest, several criteria were evaluated for hardware implementations, foremost the resource consumption, the throughput and the tradeoff between both criteria. Unfortunately, especially for lightweight and midrange implementations, a clear rationale for the design choices were missing most of the time. Therefore, in this paper a new methodology is proposed to evaluate such implementations using a new and systematic procedure. With this novel approach we show, that there are several different implementation styles to implement KECCAK with different tradeoffs. Furthermore, we substantiate the usefulness of the new methodology with several concrete and competitive implementations. These implementations are derived from our evaluation estimates and add several data points for midrange and lightweight designs to the current state of the art.